Experimental model to evaluate the gastrointestinal transit in mice (Veterinary Science, 2017)
An experimental model is described to evaluate drug action, medicinal formulations or vegetable extracts on gastrointestinal transit. Test compounds are administered to 4 mice, 30 minutes before beginning the bioessay to assure the absorption. Immediately before the essay, a per os barium sulfate solution is given and serial radiographies are taken every 30 minutes. Observing the progress of the radiopaque substance in the gastrointestinal tract, it is possible to evaluate the action of different compounds among them or with respect to a control group. This method has advantages on some others already described, since it is bloodless, reproducible, reliable and economic. These characteristics allow their regular use to detect compounds that evidence a promissory pharmacological activity
Keywords: Gastrointestinal motility; experimental model